MO618: Influence of Butyrate and Acetate on Behavior and Metabolism of Human Glomerular Microvascular Endothelial Cells. (3rd May 2022) - Novella Nicese, Maria; van den Berg, Bernard; Sol, Wendy; van Raalte, Daniël; Nieuwdorp, Max; Rotmans, Joris
Abstract: BACKGROUND AND AIMS: The gut microbiota has emerged as an important modulator of cardiovascular and renal diseases, including diabetic nephropathy (DN), one of the most common complications caused by diabetes mellitus. Importantly, diabetic patients display a reduction in bacteria producing short chain fatty acids (SCFAs) when compared with healthy individuals. SCFAs are generally associated with beneficial effects on the vascular system, as they help to reduce both oxidative stress and pro-inflammatory stimuli [1]. Although SCFAs help to protect against DN, their mechanisms of action at cell level remain largely unknown. For this reason, we aimed to study the effect of two SCFAs, butyrate and acetate, on human glomerular microvascular endothelial cells (hgMVECs) that represent one of the main components of the glomerular filtration barrier. In case of DN, glomerular endothelium shows multiple signs of dysfunction, such as uncontrolled proliferation [2], mitochondrial fragmentation [3] and monolayer disruption [4]. METHOD: hgMVECs have been exposed to different concentrations of butyrate and acetate for 24 h and/or 48 h. After treatment with SCFAs, cells have been collected for qPCR, stained for mitochondrial mass or fixated for immunocytochemistry. For the latter, we have used antibodies for the proliferation marker ki-67 and cell-to-cell junction proteins. To measure the resistance of the endothelial monolayer, electric cell-substrate impedance sensing (ECIS) was used. This system lets a current go over and between cells and the tighter the monolayer, the higher the resistance. For this type of experiment, hgMVECs have been cultured on a specific plate that is located in the ECIS machine throughout the whole experiments (before and after treatment with SCFAs). RESULTS: Butyrate decreases the number of ki-67 positive nuclei in a concentration-dependent manner, which implies lower cellular proliferation. On the other hand, at the highest concentration tested (500 uM), butyrate increases mitochondrial mass and elongation, as opposite to acetate, which does not show any effect on mitochondrial mass. These results are also supported by qPCR analysis, where it is possible to observe a decrease of genes involved in mitochondrial fragmentation upon butyrate exposure. MOreover, butyrate increases the resistance of the endothelial monolayer, as we can see in the results of the ECIS experiments. After an initial decrease, butyrate induces a steady increase of the resistance of the monolayer, which does not happen with acetate. We believe that the increase in resistance is due to a higher expression of genes and proteins involved in the formation of tight junctions. For instance, in cells treated with butyrate, gene expression of ve-cadherin, ZO-1, claudin 5 and occludin is upregulated and especially for ve-cadherin this is also observed by immunocytochemistry. CONCLUSION: Our results show that in hgMVECs, on the one hand butyrate especially can increase monolayer resistance and influence mitochondrial morphology and possibly its metabolism, while on the other hand it decreases cellular proliferation. Therefore, at cellular level, butyrate can help against several hallmarks of endothelial dysfunction Of DN.